If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x = y + -3 Reorder the terms: -7x = -3 + y Solving -7x = -3 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-7'. x = 0.4285714286 + -0.1428571429y Simplifying x = 0.4285714286 + -0.1428571429y
| (3/4)y−12=12 | | (-7)-2(2)= | | 3/4y−12=12 | | (2)-2(-2)= | | 8+3n=20 | | 3a+4b=26 | | -4x-5=-49 | | 17/3x-622 | | 3n-15=13 | | 1+3y=2.5-1.875y | | (3)-2(4)= | | 6-6x=x+1 | | 3l=l+20 | | 3=v/3.75 | | 9h^2-4=0 | | 5n-9=1 | | 3j=j+20 | | 15x+5+60=22x+4 | | 5(-6)-7(-6)= | | 2+x/6=3/5+x/30 | | 6X-4+2X+32=180 | | 5(-5)-7(0)= | | 3z+7z=33z-8(2-6)+z(8888z-7999z) | | 4x=(6x-12) | | 3x-47=40 | | 2x+10+3x+20+y=360 | | 3+4b+4=23 | | 1/5x-4=14 | | 7/12 | | y-2x=6x+4 | | (5x)(4x^2)= | | 3m-5=16-3m |